Antitumour Promoting Activity And Mode Of Action Of Methanolic Extracts Of Selected Malaysian Seaweeds And Oil Palm Fronds - Namvar, Farideh (2009)

(untitled)
Dietary and non dietary biophenols may potentially be chemoprotective against various cancers. This research aims to investigate the cancer preventive and tumoricidal properties of selected Malaysian seaweeds and oil palm leaves as a source of phenolic compounds. Initially, the anti-proliferation activities of, red (Eucheuma cottonii), green (Caulerpa lentillifera) and brown (Sargassum polycystum) seaweeds methanolic extract, against five important human cancer cell lines MCF-7, (human breast carcinoma cell line, estrogen positive) MDA-MB-231, (human breast carcinoma cell line, estrogen negative) HeLa, (human cervical adenocarcinoma cell line) HepG2, (human hepatocellular carcinoma cell line) HT-29, (human colon carcinoma) and normal Vero (African green monkey kidney cell line) were assessed. The MTT assays indicated that the 3 seaweeds extracts were cytotoxic against all these cancer cell lines in a dose-dependent manner,with Eucheuma cottonii having the greatest inhibition activity.